SRY Gene Marker Differences in Native and Crossbreed Cattle - Tety Hartatik; Dwi Ahmad Priyadi; Ali Agus; Sigit Bintara; I Gede Suparta Budisatria; Panjono Panjono; Budi Prasetyo Widyobroto; Yudi Adinata (Buletin Peternakan, 2018)
This study focused on the promoter region of the SRY gene with 1,281 bp DNA fragments, including 5'UTR, CAAT signal, and TATA box. Genomic samples of 19 cattle were obtained from Wagyu-BX (n = 2), BX (n = 5), Simmental (n = 2), Limousin (n = 2), Ongole (n = 2), Madura (n = 2), Bali (n = 2), Nellore (n = 1), and Hereford (n = 1). Two flanking primers (forward and reverse) were used for polymerase chain reaction (PCR). The PCR products were then sequenced by using a two-way primer. The obtained sequences were aligned with clustalW software to determine the differences in the nucleotide base arrangement which compiled the promoter region of the SRY gene. The cattle crossbreeding was done as an effort to improve the genetic variations and qualities. The SRY gene is a marker gene inherited from the male side (bull), so the SRY gene is expected to be used as a marker to monitor the crossbreeding. The monitoring of the crossbreed cattle is an initial effort to increase the genetic variations and enhance the genetic qualities without threatening the germplasm purity. The results of this study showed that the overall sample is monomorphic, except for Bali and Nellore cattle. Further research is needed by expanding the analysis area of the SRY gene and increasing the number of samples.